Complete Mitogenomic Analysis of the Javan Ferret-badger (Melogale orientalis): Genomic Features and Phylogenetic Relationships - Puguh Karyanto; Berliana Arkanuhaq; Niken Renawati; Bahtiar Arddun Asyafiq; Ahmad Nuruddin Khoiri (UNIVERSITAS PGRI MADIUN, 2026)
This study aims to sequence and characterize the complete mitochondrial genome of the Javan ferret-badger and to contruct its phylogenetic position within the family Mustelidae. The gDNA from the femoral muscle was extracted and subjected to Illumina whole-genome sequencing. The resulting sequence achieved a mean genome sequencing depth of approximately 1,545×. The mitochondrial genome was assembled using SPAdes v3.15.5 and annotated using MitoZ v3.4 and MITOS2. Phylogenetic relationships were analyzed against nine mustelid mitogenomes using Maximum Likelihood analysis under the GTR model with 1,000 bootstrap replicates. The circular mitogenome lenght of M. orientalis is 16,274 bp consisted of 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes, and a control region. The results showed that the mitogenome is compact with short intergenic spacers, conserved gene overlaps, and an overall GC content of 45.0%. Relative Synonymous Codon Usage analysis indicated an uneven codon distribution, with a general preference for A/T-ending codons. Mitogenomic data were used to examine the phylogenetic position of M. orientalis within Mustelidae. The analysis reveals the phylogeny of M. orientalis within Melogale supports the monophyly of the genus. These findings provide a valuable genomic data for further systematic, phylogeographic, population genetic, and conservation studies.